2000
DOI: 10.1038/35021046
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and disease control in rice

Abstract: Crop heterogeneity is a possible solution to the vulnerability of monocultured crops to disease. Both theory and observation indicate that genetic heterogeneity provides greater disease suppression when used over large areas, though experimental data are lacking. Here we report a unique cooperation among farmers, researchers and extension personnel in Yunnan Province, China--genetically diversified rice crops were planted in all the rice fields in five townships in 1998 and ten townships in 1999. Control plots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
820
7
17

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,335 publications
(888 citation statements)
references
References 20 publications
17
820
7
17
Order By: Relevance
“…Previous study showed that disease-susceptible rice planted with resistant rice had 89% greater yield and blast was 94% less severe than when they were grown in monoculture (Zhu et al, 2000). The results showed that genetic heterogeneity provides greater disease suppression.…”
Section: Tablementioning
confidence: 90%
“…Previous study showed that disease-susceptible rice planted with resistant rice had 89% greater yield and blast was 94% less severe than when they were grown in monoculture (Zhu et al, 2000). The results showed that genetic heterogeneity provides greater disease suppression.…”
Section: Tablementioning
confidence: 90%
“…However, these examples are very promising as the corresponding plants show high levels of resistance against several pathogens, and when this was measured, no side effect was observed. Mixed planting of transgenic lines should also be efficient for controlling disease epidemics as shown using wild-type mixtures for blast resistance (Zhu et al 2000).…”
Section: Conclusion and Recommendations For Future Transgenic Approamentioning
confidence: 99%
“…The cultivar or plant species are totally mixed (mixed intercropping) or arranged in alternate rows or in strips (row intercropping) (Ghaley et al 2005;Pelzer et al 2012). The number of associated plant species or cultivars can vary, but there are usually two species, such as a cereal and a legume, or two to four cultivars of the same species (Zhu et al 2000;Mundt 2002). In group B (relay or sequential cropping), plants are not grown together at the same time but in crop sequences.…”
Section: Plant Diversity In Multiple Cropping Systemsmentioning
confidence: 99%
“…For instance, cereal crops can disrupt insects in their visual search for smaller crops (Ogenga-Latigo et al 1992) or prevent dispersal by wind. Resource dilution and habitat fragmentation were both shown to contribute to the efficient control of disease in crop associations in lowinput farming, with various success stories for cereals (Zhu et al 2000;Mundt 2002).…”
Section: Multiple Cropping Systems To Reduce the Use Of Pesticidesmentioning
confidence: 99%